Bergson, précurseur des mobilités académiques contemporaines ? - Fred Dervin (Les Cahiers de Framespa)
At the beginning of the 20th Century the philosopher Henri Bergson (1859-1941) was largely « mobile ». Professor at the Collège de France in the 1910s, Bergson travelled regularly to Britain (Birmingham, Cambridge, Edinburg, London and Oxford) and to the United States (New York) to give a series of talks and attend conferences. In this paper I shall examine what motivated the philosopher to be mobile, who invited him and why. I shall also demonstrate how Bergson supported academic mobility through his personal and political actions. The corpus use is based on articles from the New York Times and the Times as well as letters written by Bergson and a recent biography of the scholar. The main issue tackled in the paper is: can Bergson be considered as a forerunner of the contemporary hypermobile scholar?